Contribuição ao estudo da frequência de sintomas subjetivos, relatados como queixa principal, por pacientes com disfunção craniomandibular - Oliveira, Wagner de [UNESP] (1992)
We surveyed subjective symptoms of 600 patients referred to the Occlusion and Craniomandibular Dysfunction Center of the School of Dentistry, Campus of São José dos Campos São Paulo, Brazil. We have only considered those symptoms reported by the patients as major complaints. Our purpose on this project was to draw a profile of the disease considering sex, age and incidence of the symptoms that presented themselves or associated with others. Findings were that we found a significant larger number of women, 82.83%, comparing with 17.17% of men. Most of the patients belonged to the third decade, followed by the fourth and second. The most frequent symptom was pain on TMJ region, 42%, followed by TMJ noises, 26.6%, facial pain, 15.5%, earache, 14.5% and headache, 12.1%. The symptom TMJ noises showed to be statistically more significant in men, while headaches, pain in the neck region and temporary locking were more frequent in women. The most frequent association between two symptoms was: TMJ noises with TMJ pain, earache with headache and TMJ pain with earache. There was no statistical difference between sexes. The most frequent association of three symptoms was: TMJ noises together with TMJ pain and pain or difficulty in chewing